ANÁLISE DO INDICADOR DE PRODUTIVIDADE GLOBAL DE CONSTRUTORAS CEARENSES - Rocha, Paulo Henrique Gomes da; Silva, Raymundo Robson Gomes da; Silva Filho, Washington Bastos da; Barros Neto, José (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In an environment of high competition between companies and a recession in sales, one solution is to optimize production. In the technical area, there is a current lack of effective tools for measuring and managing labor productivity, generating a lack of assertiveness of budgets and planning. In order to reach the objectives, the methodology of this study was divided into two phases: field research and database analysis. The first phase contemplates field research in construction companies in Ceará, in order to verify the current way in which they work in the calculation of their productivity indexes. The second phase is an analysis of the database of an ERP, where there are data collected from several works and companies from Ceará, allowing an observation of which data are most collected in the field by the managers. Finally, the association between ERP input data type and current productivity measurement methodology in the current market should indicate the ability of a set of constructors that use the same ERP to use the same methodology for productivity measurement index and perhaps, to promote an instrument that allows the comparison between works and / or between companies of the civil construction sector.